DETECTION OF SPEECH IN REAL-TIME SIGNAL - D. A. Barysevich; H. V. Davydau; V. A. Papou (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
Information parameters of the speech signals, allowing to allocate sites of processed information with speech signals in real time, is considered. Modeling in MatLab is executed to detect speech signals in real time.